2018
DOI: 10.46653/jhst180101008
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Aloe vera Gel, Chitosan and Sodium Alginate Based Edible Coatings on Postharvest Quality of Refrigerated Strawberry Fruits of cv. Chandler

Abstract: Strawberry is a non-climacteric fruit but exhibits very limited postharvest life due to rapid softening and decay. Therefore, the current study was carried out to evaluate the effects of different types of edible coatings to extend the postharvest life of strawberry fruit. The strawberry fruits of cultivar Chandler, grown under agro-climatic conditions of Multan, were coated with Aloe vera gel, chitosan (2%) or sodium alginate (2%) and kept in refrigerated storage at 5-7 °C with 50-60% RH for 12 days. The frui… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 47 publications
2
13
0
Order By: Relevance
“…Strawberries coated with alginate-AA-LDHs show a lower declining rate of the total phenolic content due to the lower permeability of oxygen because the ascorbic acid in the coating effectively oxidizes the oxygen . Similar results have been obtained in previous work for chitosan and sodium alginate-coated refrigerated strawberries . Specifically, alginate coatings with the incorporation of antimicrobial agents are effective in the maximum retention of phenolic compounds inside the fruits …”
Section: Resultssupporting
confidence: 84%
“…Strawberries coated with alginate-AA-LDHs show a lower declining rate of the total phenolic content due to the lower permeability of oxygen because the ascorbic acid in the coating effectively oxidizes the oxygen . Similar results have been obtained in previous work for chitosan and sodium alginate-coated refrigerated strawberries . Specifically, alginate coatings with the incorporation of antimicrobial agents are effective in the maximum retention of phenolic compounds inside the fruits …”
Section: Resultssupporting
confidence: 84%
“…Application of ALV gel coating have been found to actively preserve the titratable acidity and accumulation of SSC and sugar-to-acid ratio during storage by delaying senescence in fruits and vegetables. Numerous reports about fresh horticultural produce such as tomato (Khatri et al, 2020), litchi (Ali et al, 2019a), orange (Rasouli et al, 2019), mango (Atlaw, 2018), strawberry (Qamar et al, 2018), TA B L E 3 Effect of Aloe vera application on postharvest disease incidence of fruits and jujube (Mani et al, 2017) supported this statement and revealed that coated fruits displayed maintained acidity and better consuming quality. ALV gel coating has been found to reduce the degeneration in organic acids with maintenance of sugar-to-acid ratio at higher level.…”
Section: Phytonutrients and Antioxidative Capacitymentioning
confidence: 79%
“…Polygalactonurase (PG) is the key hydrolytic enzyme involved in firmness loss caused by degradation of the middle lamella cell wall (Maringgal et al, 2020). ALV gel coated fruits showed significantly higher firmness in tomatoes (Firdous et al, 2020), sapodilla (Khaliq, Ramzan, et al, 2019), orange (Rasouli et al, 2019), nectarines (Paladines et al, 2014), strawberry (Qamar et al, 2018), fig (Marpudi et al, 2013), and pineapple (Adetunji et al, 2012) fruits, etc. ALV coatings have also been reported to reduce the moisture loss in all fruits and vegetables (Table 2).…”
Section: Weight Loss and Firmnessmentioning
confidence: 99%
“…Aloe vera and chitosan coating on strawberries showed increasing trend of anthocyanin contents during storage. However, the treatments were not significant (Qamar et al., 2018). The increase in anthocyanin content of strawberries may be due to biosynthesis of compounds during storage period (Sogvar et al., 2016).…”
Section: Resultsmentioning
confidence: 99%